Purchasing Behaviors of Online Tutoring Courses of Senior High School Students in Extra-Large Schools in Nakhon Si Thammarat Province - Kwansud, Pimonpan; Compan, Pongpan (Science, Technology, and Social Sciences Procedia, 2023)
This study has 3 main objectives: 1) Studying the purchasing behavior of online tutoring courses of high school students in a large special school in Nakhon Si Thammarat Province. 2) Studying the factors related to purchasing behavior. Online tutoring courses for high school students in extra-large schools in Nakhon Si Thammarat Province. The research results found that Most of the respondents were female. Currently studying in Grade 12 with a cumulative grade point average of 2.01 - 2.50 Currently studying at Thung Song School. Parents of the majority of respondents’ Occupation a state enterprise employees. The median income for most families is 15,001 - 25,000 baht. Students receive news about online courses through the YouTube channel. The reason for taking online tutoring is to review knowledge for exams in school. The cost of tutoring per course is 4,001 - 6,000 baht. Most choose to study Chemistry, Physics, and Biology.